2021
DOI: 10.1039/d1ra07691d
|View full text |Cite
|
Sign up to set email alerts
|

Structure modulation of g-C3N4in TiO2{001}/g-C3N4hetero-structures for boosting photocatalytic hydrogen evolution

Abstract: The structure of g-C3N4 in the prepared TiO2{001}/g-C3N4 hetero-structures could be modulated from BCN to CN-NS, CN-NC or CN-QD by tuning the synthetic temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The Brunauer–Emmet–Teller (BET) studies were carried out for all photocatalysts to elucidate the impact of the heterojunction construction between g-C 3 N 4 and ZnO, and NPs decoration on their textural characteristics (Figure S7). The BET profiles associated with g-C 3 N 4, ZnO, g-C 3 N 4 /ZnO heterojunction, and Pd decorated heterojunction show that the materials are porous and the Pd-decorated heterojunction display characteristics of a type II adsorption and H 3 loop . These features signify the interparticle porosity within the nanocomposites .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The Brunauer–Emmet–Teller (BET) studies were carried out for all photocatalysts to elucidate the impact of the heterojunction construction between g-C 3 N 4 and ZnO, and NPs decoration on their textural characteristics (Figure S7). The BET profiles associated with g-C 3 N 4, ZnO, g-C 3 N 4 /ZnO heterojunction, and Pd decorated heterojunction show that the materials are porous and the Pd-decorated heterojunction display characteristics of a type II adsorption and H 3 loop . These features signify the interparticle porosity within the nanocomposites .…”
Section: Resultsmentioning
confidence: 69%
“…The BET profiles associated with g-C 3 N 4, ZnO, g-C 3 N 4 /ZnO heterojunction, and Pd decorated heterojunction show that the materials are porous and the Pd-decorated heterojunction display characteristics of a type II adsorption and H 3 loop. 52 These features signify the interparticle porosity within the nanocomposites. 53 This observation sheds light on the porous structure of the synthesized materials developed due to the formation of a nanocomposite of ZnO and g-C 3 N 4 .…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…[ 19 ] The XRD pattern of g‐C 3 N 4 NSs revealed diffraction peaks at 12.6°, 21.7°, and 27.6° corresponding to the (0 0 1), (1 0 0), and (0 0 2) crystal faces of carbon nitride C 3 N 4 (JCPDS 87–1526). [ 20 ] The XRD results indicated that Fe 3 O 4 NPs, MnO 2 NSs, and g‐C 3 N 4 NSs were successfully modified on the fiber substrates. Furthermore, N 2 isothermal adsorption‐desorption curves and corresponding DFT pore size distributions were employed to investigate the specific surface area ( S BET ), total pore volume ( V pore ), average pore diameter ( D pore ), and pore structure of samples.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] Moreover, g-C 3 N 4 has a narrow band gap value of 2.6 eV and is easily hybridized with other wide-band gap semiconductors to form a composite, which is an ideal photocatalytic reaction material. 41,42 Based on the above discussion, TiO 2 NSs with uniform morphology were prepared, and g-C 3 N 4 was combined with TiO 2 to form a g-C 3 N 4 @TiO 2 composite, which was applied to the photoanode, which not only enabled the material to obtain a larger specific surface area, but also improved the stability of the material. It is concluded by various electrochemical characterization methods that the g-C 3 N 4 @TiO 2 composite photoanode corresponding to the cell shows the best photoelectric performance, with its current density ( J sc ) = 26.5 mA cm −2 , photoelectric conversion efficiency (PCE) = 8.2%, open circuit voltage (V oc ) = 0.62 eV, and a filling factor (FF) = 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…38–40 Moreover, g-C 3 N 4 has a narrow band gap value of 2.6 eV and is easily hybridized with other wide-band gap semiconductors to form a composite, which is an ideal photocatalytic reaction material. 41,42…”
Section: Introductionmentioning
confidence: 99%